In Silico Study of Bioactive Compounds from Acalypha indica L. Interacting with the COX-2 Receptor as Potential Anti-Inflammatory Candidates - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Acalypha indica L. is a medicinal herb traditionally used across Asia for treating inflammation-related conditions. Although several studies report anti-inflammatory activity in its extracts, little is known about the molecular interaction of its individual phytochemicals with cyclooxygenase-2 (COX-2)—a validated therapeutic target for inflammatory diseases. This study fills this gap by performing a comprehensive in silico analysis of 20 major bioactive compounds of A. indica using molecular docking, binding interaction profiling, and ADMET predictions. Docking against the COX-2 receptor (PDB: 3LN1) using AutoDock Vina revealed that rutin (-10.4 kcal/mol), kaempferol-3-O-rutinoside (-10.1 kcal/mol), quercetin (-9.6 kcal/mol), and luteolin (-9.3 kcal/mol) demonstrated strong predicted affinity and stable interactions with key residues Arg120, Tyr355, and Tyr385, comparable to celecoxib (-10.8 kcal/mol). ADMET profiling showed that aglycone flavonoids possessed more favorable drug-likeness properties than glycosides. These results suggest that A. indica contains multiple promising lead compounds for future COX-2 inhibition studies and highlight the molecular mechanisms supporting its ethnomedicinal use as an anti-inflammatory agent.